1987
DOI: 10.1016/0022-0728(87)80259-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical faceting and preferred cyrstallographic orientation of rhodium electrodes

Abstract: The electrochemical faceting of Rh in 1 M HaSO, can be developed by applying repetitive periodic potentials in the range -0.1 to 1.2 V (vs. RHE) at frequencies greater than 0.5 kI-Iz. The degree of electrochemical faceting, as followed voltammetrically at 0.1 V/s in the H-adatom potential range, exhibits two different situations, depending on the lower and upper limits of the periodic potential. In one case, the voltammogram exhibits two sharp reversible conjugated peaks related to the H-adatom reactions, simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…For values of u > 1000 V/s, the predominant effect is the increase in sharpness of the H-adatom current peaks. This effect is to some extent similar to that recently observed for the electrochemical faceting of pc rhodium in acids [4].…”
Section: Voftammetric Changes Of Rh5d~~m Electrodes Produced By Rtpssupporting
confidence: 89%
See 1 more Smart Citation
“…For values of u > 1000 V/s, the predominant effect is the increase in sharpness of the H-adatom current peaks. This effect is to some extent similar to that recently observed for the electrochemical faceting of pc rhodium in acids [4].…”
Section: Voftammetric Changes Of Rh5d~~m Electrodes Produced By Rtpssupporting
confidence: 89%
“…Depending on how the periodic potential is applied to the electrode, two relevant limiting situations can be accomplished. The first concerns the electrochemical faceting of the electrode surface and the development of a preferred crystallographic orientation implying a negligible increase in the electrode active area [2,3], which, for the case of rhodium, was extensively dealt with in a previous publication [4]. The second comprises significant changes in the active electrode area provoked through the electroformation of a thick oxide layer by means of fast periodic potentials and further single sweep electroreduction [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Similar types of processes occur also for Pd (100) single crystals [14]. This paper is devoted to investigating morphological changes produced on the surface of Pd electrodes in acid by periodic potential treatments similar to those employed in the electrochemical faceting of other metals such as Pt [1,2], Au [15] and Rh [16]. Roughening and electrochemical faceting conditions for Pd can be modified substantially by changing the frequency and potential window of the periodic potential applied to the electrode, although the lack of electrochemical data concerning the electrochemical adsorption behaviour of single crystal Pd surfaces impedes definitive characterisation of the surface modifications.…”
mentioning
confidence: 95%
“…1 and 2 as three potential values (denoted by arrows) characteristic for the hydrogen adsorption/desorption pair, ''doublelayer'' region and reversible part of the oxy(hydroxide) film formation [1][2][3][4][9][10][11]15]. At three different potential values, different shapes of impedance spectra are obtained with either different u plots, or different numbers of characteristic break frequencies or ''bends'', denoting positions of changing slopes in log jZ el j [31].…”
Section: Resultsmentioning
confidence: 99%
“…Utility of application of the electrochemical impedance spectroscopy (EIS) for the rhodium electrode in this potential region can be easily predicted from the literature concerned on voltammetry [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], radiochemical coverage experiments [9,[17][18][19][20], electrochemical quartz crystal microbalance technique [20,21], and surface spectroscopy [8,16,[22][23][24][25] of various kinds of rhodium (smooth polycrystalline, single-crystal, ad-layer, and rhodized) electrodes. Almost all of these studies commonly suggested the presence of different adsorption phenomena in this region of polarisation potentials, including under-potential deposition (UPD) of hydrogen at potentials positive to the reversible H þ /H 2 potential, adsorption of various (an)ions present in electrolyte solutions, and adsorption of oxygen containing species prior to formation of the bulk oxides.…”
Section: Introductionmentioning
confidence: 99%